Comparison of customized and cohort-based birthweight standards in identification of growth-restricted infants in GUSTO cohort study. (2nd August 2016) - Agarwal, Pratibha; Rajadurai, Victor Samuel; Yap, Fabian; Yeo, George; Chong, Yap-Seng; Kwek, Kenneth; Saw, Seang Mei; Gluckman, Peter D.; Lee, Yung Seng; ,; Tan, Kok Hian
Abstract: Background : The aim was to evaluate the ability of customized and cohort birthweight standards in discriminating intrauterine growth retardation (IUGR). Methods : Birthweights (BWs) of GUSTO singleton infants born at gestational age (GA) 35–41 weeks were converted using two standards: (a) GUSTO cohort-based BW centile adjusted for GA and baby gender; (b) customized BW percentile calculator adjusted for maternal height and weight, race, parity, GA and gender. Infants were classified into three groups: (1) < 10th BW centile by customization– customized-SGA, (2) < 10th BW centile by GUSTO– GUSTO-SGA; and (3) > 10th BW centile by both standards – BOTH-non-SGA. Results : Of the 1011 infant–mother dyads, 68 were customized-SGA and 104 were GUSTO-SGA, with concordance of 61% ( n = 63) for SGA. While 5 (7%) of customized-SGA were not SGA by GUSTO-charts, 41 (39%) of GUSTO-SGA were not SGA by customized-charts. Customized-SGA had significantly the least growth in abdominal circumference (AC) and highest head circumference (HC): AC growth ratio between second and third trimester; and the lowest mean BW, ponderal index and placental weight than other groups. Conclusion : Customized-SGA standard was a better discriminator of pathologic fetal growth based on AC growth. It improved strength of association with pathology and in our population reduced false positives (41/104 = 39%) in the assessment of SGA.